ChinaSpec: A Network for Long‐Term Ground‐Based Measurements of Solar‐Induced Fluorescence in China. Issue 3 (26th March 2021) - Zhang, Yongguang; Zhang, Qian; Liu, Liangyun; Zhang, Yangjian; Wang, Shaoqiang; Ju, Weimin; Zhou, Guangsheng; Zhou, Li; Tang, Jianwu; Zhu, Xudong; Wang, Feng; Huang, Ying; et al.
Abstract: Remotely sensed solar‐induced fluorescence (SIF) has emerged as a novel and powerful approach for terrestrial vegetation monitoring. Continuous measurements of SIF in synergy with concurrent eddy covariance (EC) flux measurements can provide a new opportunity to advance terrestrial ecosystem science. Here, we introduce a network of ground‐based continuous SIF observations at flux tower sites across the mainland China referred to as ChinaSpec. The network consists of 16 tower sites until 2019 including six cropland sites, four grassland sites, four forest sites, and two wetland sites. An automated SIF system was deployed at each of these sites to collect continuous high‐resolution spectra for high‐frequency SIF retrievals in synergy with EC flux measurements. The goal of ChinaSpec is to provide long‐term ground‐based SIF measurements and promote the collaborations between optical remote sensing and EC flux observation communities in China. We present here the details of instrument specifications, data collection and processing procedures, data sharing and utilization protocols, and future plans. Furthermore, we show the examples how ground‐based SIF observations can be used to track vegetation photosynthesis from diurnal to seasonal scales, and to assist in the validation of fluorescence models and satellite SIF products (e.g., from OCO‐2 and TROPOMI) with the measurements from these sites since 2016. This network of SIF observations could improve our understanding of the controls on the biosphere‐atmosphere carbon exchange and enable the improvement of carbon flux predictions. It will also help integrate ground‐based SIF measurements with EC flux networks which will advance ecosystem and carbon cycle researches globally. Key Points: ChinaSpec is a recently established network of ground‐based solar‐induced fluorescence (SIF) measurements We present an introduction on the current status and challenges of ChinaSpec ChinaSpec now consists of 16 tower sites including six cropland sites, four grassland sites, four forest sites, and two wetland sites